Polymorphisms of chemokine and chemokine receptor genes in idiopathic immune-mediated posterior segment uveitis - Ahad, Muhammad A. (Molecular Vision, 2007)
PURPOSE: Chemokines are important inflammatory mediators that play a crucial role in uveitis. Polymorphisms in chemokine genes can alter the expression of these genes in the inflammatory cells, which, in turn, can affect the clinical phenotype of the disease. The purpose of this study was to identify polymorphisms in chemokine genes that can predict visual outcome in patients with immune-mediated posterior segment uveitis. METHODS: This is a case-control study of 141 Caucasians with idiopathic immune-mediated posterior segment uveitis and 282 controls matched by age and ethnicity. Six polymorphisms in four genes, (MCP-1-2518A/G, RANTES-403G/A, RANTES-28C/G, CCR2 V64I, CCR5-59029G/A, and CCR5 32 bp deletion) were analyzed by sequence specific primers polymerase chain reaction. RESULTS: Patients with G allele at MCP-1-2581 developed the disease at an early age as compared to patients with A allele corrected p value pc=0.003. Also patients with A allele at RANTES-403 position developed less severe disease and had better visual outcome when compared with patients with G allele (pc=0.02) Final visual acuity after 18 months was better in patients with 32 bp deletion of the CCR5 gene and in patients with the CCR2 wild-type genotype pc=0.02 and pc=0.04, respectively. Patients with the CCR2 64I allele also had a higher risk of developing an elevated intraocular pressure as compared to patients with the wild-type genotype (pc=0.007). CONCLUSIONS: Though the utility for prediction of disease susceptibility of the studied polymorphisms in chemokine genes is in general not robust, we have found that polymorphisms in chemokine genes can influence the outcome of patients with idiopathic immune-mediated posterior segment uveitis. These associations require further analysis in other groups of patients.